Investing in the behavioural dimensions of transnational cooperation: a personal assessment of the Managing Global Governance (MGG) Programme - Thomas Fues (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
This text sums up the author's personal experiences and insights as former staff member responsible for the Managing Global Governance (MGG) Programme, funded by the Federal Ministry for Economic Cooperation and Development / Bundesministerium für wirtschaftliche Zusammenarbeit und Entwicklung (BMZ) and implemented by the German Development Institute / Deutsches Institut für Entwicklungspolitik (DIE). The overarching goal of the MGG Programme is to enhance transnational knowledge cooperation for global sustainable development, based on a behavioural theory of change. As the extensive collaboration under the MGG umbrella demonstrates, partner countries share with the German side a preference for the global common good, despite the predominance of domestic concerns for poverty reduction and growth on their side. Over the years, MGG has generated a broad canvas of joint activities in knowledge creation, policy dialogue and training by engaging with a diverse set of actors from governments, think tanks, academia and, to a lesser extent, civil society and business. Two independent evaluations commissioned by DIE, as well as numerous statements by partners and alumni, provide ample evidence that the MGG Programme has fulfilled the defined goals. With an increased number of activities and integration of new sectors, it seems advisable to consolidate MGG by introducing formal arrangements for membership and governance through a memorandum of understanding to be signed by interested institutions.
Keywords: 330; Agenda 2030; Wissenskooperation